An Analysis of Retention Viewed from Physics Outcomes of Students in Class XI MIPA SMA Negeri 1 Takalar - Rini Rini; Nurazmi Nurazmi; Ma'ruf Ma'ruf (Universitas Muhammadiyah Makassar, 2020)
This study aims to describe how much the physics learning outcomes of Class XI MIPA students in SMA Negeri 1 Takalar and to analyze the retention profile of XI MIPA students at SMA Negeri 1 Takalar. This research was conducted in September to October 2019. The type of research used was descriptive research. Samples were taken using simple random sampling technique, namely by drawing a class that will be used as a research class. The research instrument used was a test instrument in the form of descriptive questions. Data from test instruments, analyzed by descriptive test. The results showed that the physics learning outcomes of MIPA XI grade students at SsMA Negeri 1 Takalar were in the high category with an average score of 67.27 and the retention power of students at XI MIPA class at SMA Negeri 1 Takalar included in the category with a sufficient percentage of 30%.